Management reporting of the enterprise: content characteristics and specific nature of its formation - Voskresenska, T.; Dzoba, N. (Lviv Politechnic Publishing House, 2018)
The necessity of management reporting formation by the enterprise with the purpose of providing efficient administrative decisions to increase its competitiveness and achieve strategic goals is examined and substantiated. The basic problems of management reporting formation by the enterprise, which are connected: with the complexity of gathering, substantiation, storage and processing of data are singled out; incomprehensibility of the formation procedure and purpose of the reports, as well as the contradiction and lack of data integrity; insufficient analytical processing of information to support the strategic and operational management decision-making; lack of qualified specialists in the interpretation of management reporting, its analysis and responsibility for management decision-making. The influence of resource provision (financial, informational, methodological, organizational and technical) on the qualitative characteristics of the management reporting system is researched. The possible advantages and disadvantages of management system formation of the enterprise are identified and summarized. The expediency of management reporting formation in accordance with the level of enterprise governance in the context of three generalized types is substantiated: strategic – is provided to top managers during the reporting period or on request; tactical – is provided to linear managers with the appropriate periodicity of the output, operational – is provided to specialists daily or in the current time. It is determined that the combination of reporting under IFRS and management reporting in a single information system will increase the efficiency of the management decisions made on its basis. The conclusions emphasize the need to develop relevant sectoral methodological recommendations, the definition of a targeted methodology for management reporting formation and the establishment of its indicative indicators.
Keywords: management accounting; management reporting; types of management reporting; management reporting system; format of management reporting; 657.631